Answer:
To calculate the vertex you can use the vertex form ( i searched about the vertex and found it) but i don't know how to use it so i used another method.
The vertex is where the function inverts (y values) so it is going to be or a maximum or a minimum of the function. To calculate the min/max you derivate the function and then equal it to zero.
1) y = -3x^2 -12x -10
the derivative of y is y' = -6x -12 = -6(x+2)
y'=0 <=> -6(x+2) = 0 <=> x+2=0 <=> x=-2
y(-2) = -3(-2)^2 -12*(-2) -10 = 2
So the vertex is the point (-2,2) .
Because the slope of the equation is negative that means that the vertex is going to be the maximum , so the maximum is (-2,2) .
To find another 4 points you just have to pick values of x and replace them in the equation y = -3x^2 -12x -10 to find y.
2) y = -2x^2 -12x -16
Do the same thing we did in point 1
y'= -4x-12 = -4(x+3)
y'=0 <=> -4(x+3) = 0 <=> x+3=0 <=> x=-3
y(-3) = -2(-3)^2 -12*(-3) -16 = 2
So the vertex is the point (-3,2) .
What is -2 + 5(9 − 12)
Answer:
-17
Step-by-step explanation:
-2 + 5(9 − 12)
PEMDAS
Parentheses first
-2 + 5(-3)
Then multiply
-2 -15
Subtract
-17
Answer:
-17
Step-by-step explanation:
hope this helps
U need help ASAP!!!Please explain the answer
At the mall you spent a total of $170.86. You bought 2 pairs pf jeans for $39.95 each, a jacket for
$45.99, and shirts for $14.99 each. How many shirts did you buy?
Answer:
3
Step-by-step explanation:
Total Money Spent = $170.86
Cost of each jeans = $39.95x2 = 79.9
Cost of each Jacket = $45.99
Cost of each shirt = $14.99
=79.9 + 45.99
=125.89
=170.86 - 125.89
=44.97
=44.97 / 14.99
=3
Answer From Gauth Math
Suppose a line passes through (a, -11) and (7,13), and is parallel to the line
y =2x + 8, What is the value of a? Write the equation of the line
Answer:
a=19
Step-by-step explanation:
The slope of the equation is - 2 as it's parallel to the given line. Using two point slope form, (13-(-11))/(7-a)=-2. 24=-2(7-a), - 12=7-a, a=19
Answer:
see explanation
Step-by-step explanation:
The equation of a line in slope- intercept form is
y = mx + c ( m is the slope and c the y- intercept )
y = 2x + 8 ← is in slope- intercept form
with slope m = 2
Parallel lines have equal slopes
Calculate the slope between the 2 given points and equate to 2
Using the slope formula
m = [tex]\frac{y_{2}-y_{1} }{x_{2}-x_{1} }[/tex]
with (x₁, y₁ ) = (a, - 11) and (x₂, y₂ ) = (7, 13)
m = [tex]\frac{13-(-11)}{7-a}[/tex] = [tex]\frac{13+11}{7-a}[/tex] = [tex]\frac{24}{7-a}[/tex] , then
[tex]\frac{24}{7-a}[/tex] = 2 ( multiply both sides by 7 - a )
2(7 - a) = 24 ( divide both sides by 2 )
7 - a = 12 ( subtract 7 from both sides )
- a = 5 ( multiply both sides by - 1 )
a = - 5
--------------------------------------------------
y = 2x + c ← is the partial equation
To find c substitute (7, 13) into the partial equation
13 = 14 + c ⇒ c = 13 - 14 = - 1
y = 2x - 1 ← equation of parallel line
Two more than 4 times the cube of a number is 34.
Answer:
2
Step-by-step explanation:
4x^3 + 2 = 34
4x^3 = 32
x^3 = 8
x=2
which of the following represents x= 1/2 y written in general form?
2x-y = 0
=============================================
Work Shown:
x = (1/2)y
2x = y ... multiply both sides by 2
2x-y = 0 ... subtract y from both sides
This is in standard form Ax+By = C, where A,B,C are integers. In this case, A = 2, B = -1, C = 0.
If x+y = nx+2 then x equals
Answer:
x+y = nx+2
⇔x-nx = 2-y
⇔x(1-n) = 2-y
⇔x = (2-y)/(1-n)
Answer:
Hello,
Step-by-step explanation:
x+y=nx+2
x-nx=2-y
x(1-n)=2-y
if 1-n ≠0 (or n≠1) then
[tex]x=\dfrac{2-y}{1-x}[/tex]
Help me with this pls !
Answer:
awnser G
Step-by-step explanation:
Answer:
H
Step-by-step explanation:
y and x² are corresponding angles and are congruent, that is
y = x²
Then
[tex]\frac{y^3}{3}[/tex] = [tex]\frac{(x^2)^{3} }{3}[/tex] = [tex]\frac{x^6}{3}[/tex] → H
Find the distance between R(-5,-3) and S(4,-2).
Answer:
√106
Step-by-step explanation:
to calculate the distance between two points on an xoy plane you use the formula
√(x2-x1)²+(y2-y1)²
in this case x1 is -5,x2 is 4,y1 is -3 and y2 is -2 therefore the solution will be
√(4-(-5)²+(-2-3)²
√(4+5)²+(-5)²
√(9)²+(-5)²
√81+25
√106
I hope this helps
Solve the system using substitution.
X = Y-4
2x + 3y = 12
Answer:
Step-by-step explanation:
If you know that x = y - 4, you can plug that value into the equation 2x + 3y = 12 for x. This would look like:
2(y - 4) + 3y = 12
Simplify:
2y - 8 + 3y = 12
5y - 8 = 12
add 8 to both sides
5y = 20
divide both sides by 5
y = 4
Now, substitute y = 4 back into the equation x = y - 4:
x = 4 - 4
and simplify:
x = 0
This means that the answer is x = 0 and y = 4.
Answer:
(0, 4 )
Step-by-step explanation:
Given the 2 equations
x = y - 4 → (1)
2x + 3y = 12 → (2)
Substitute x = y - 4 into (2)
2(y - 4) + 3y = 12 ← distribute and simplify left side
2y - 8 + 3y = 12
5y - 8 = 12 ( add 8 to both sides )
5y = 20 ( divide both sides by 5 )
y = 4
Substitute y = 4 into (1) for corresponding value of x
x = 4 - 4 = 0
solution is (0, 4 )
sin^6x + cos^6x = 1/4
Answer:
[tex]\displaystyle x = \frac{\pi}{4} + k\, \pi[/tex] for integer [tex]k[/tex] (including negative numbers.)
Step-by-step explanation:
Pythagorean Identity: [tex]\sin^{2}(x) + \cos^{2}(x) = 1[/tex]. Equivalently, [tex]\cos^{2}(x) = 1 - \sin^{2}(x)[/tex].
Rewrite the original equation and apply this substitution to eliminate [tex]\cos(x)[/tex]:
[tex]\displaystyle \sin^{6}(x) + \cos^{6}(x) = \frac{1}{4}[/tex].
[tex]\displaystyle (\sin^{2}(x))^{3} + (\cos^{2}(x))^{3} = \frac{1}{4}[/tex].
[tex]\displaystyle (\sin^{2}(x))^{3} + (1 - \sin^{2}(x))^{3} = \frac{1}{4}[/tex].
Let [tex]y = \sin(x)[/tex] ([tex]-1 \le y \le 1[/tex].) The original equation is equivalent to the following equation about [tex]y[/tex]:
[tex]\displaystyle y^{6} + (1 - y^{2})^{3} = \frac{1}{4}[/tex].
Expand the cubic binomial in the equation:
[tex]\displaystyle y^{6} + 1 - 3\, y^{2} + 3\, (y^{2})^{2} - (y^{2})^{3} = \frac{1}{4}[/tex].
[tex]\displaystyle y^{6} + 1 - 3\, y^{2} + 3\, y^{4} - y^{6} = \frac{1}{4}[/tex].
Simplify to obtain:
[tex]\displaystyle 1 - 3\, y^{2} + 3\, y^{4} = \frac{1}{4}[/tex].
Rearrange and simplify:
[tex]12\, y^{4} - 12\, y^{2} + 3 = 0[/tex].
[tex]3\, (2\, y^{2} - 1)^{2} = 0[/tex].
[tex]2\, y^{2} - 1 = 0[/tex].
[tex]\displaystyle y^{2} - \frac{1}{2} = 0[/tex].
Solve for [tex]y[/tex]:
Either [tex]\displaystyle y = \frac{1}{\sqrt{2}}[/tex] or [tex]\displaystyle y = -\frac{1}{\sqrt{2}}[/tex].
If [tex]\displaystyle \sin(x) = y = \frac{1}{\sqrt{2}}[/tex], then [tex]\displaystyle x = \frac{\pi}{4} + 2\, k\,\pi[/tex] for all [tex]k\in \mathbb{Z}[/tex].
On the other hand, if [tex]\displaystyle \sin(x) = y = \frac{1}{\sqrt{2}}[/tex], then [tex]\displaystyle x = \frac{3\, \pi}{4} + 2\, k\,\pi = \frac{\pi}{4} + (2\, k + 1) \, \pi[/tex] for all [tex]k\in \mathbb{Z}[/tex].
Combine both situations to obtain:
[tex]\displaystyle x = \frac{\pi}{4} + 2\, k\, \pi[/tex] for all [tex]k \in \mathbb{Z}[/tex].
Which is 1/3+1/4?
FASTBRIDGE!!
Option B is 1/3 + 1/4.
1/3 + 1/4 is equal to 7/12.
Here, we have,
To find the sum of 1/3 and 1/4, you need to have a common denominator.
The common denominator of 3 and 4 is 12.
To make the fractions have the same denominator, you can convert them as follows:
1/3 = (1/3) * (4/4) = 4/12
1/4 = (1/4) * (3/3) = 3/12
Now that both fractions have a denominator of 12, you can add them together:
1/3 + 1/4 = 4/12 + 3/12 = (4+3)/12 = 7/12
Therefore, 1/3 + 1/4 is equal to 7/12.
now, from the given options, we have,
in option B. it is indicating that,
2/6 + 1/4
=> 1/3 + 1/4.
Hence, Option B is 1/3 + 1/4.
To earn more on addition click:
brainly.com/question/29560851
#SPJ6
PLS HELP ME ON THIS QUESTION I WILL MARK YOU AS BRAINLIEST IF YOU KNOW THE ANSWER!!
Find the mode of the data set that consists of 8, 18, 4, 2, 3, 7, 11, 13, 5, 1.
A. 6
B. 7.2
C. no mode
D. 17
Answer:
No mode
Step-by-step explanation:
There are no any numbers which are repeated. So there is no mode.
Answer:
The answer is C.no mode because the mode of a data set is the number that occurs most frequently in the set. To easily find the mode, but the numbers in order from least to greatest and count how many times each number occurs. The number that occurs the most is the mode!
Does this graph represent a function (scatter)
A. Yes
B. No
Answer:
A. Yes
Step-by-step explanation:
it is always yes because no os negative
Answer
a
Step-by-step explanation:
it does represent a function
What's 179 square root
Show how
Answer:
The square root of 179 rounded up to 7 decimal places is 13.3790882. It is the positive solution of the equation x² = 179.
PLS HELP ME ON THIS QUESTION I WILL MARK YOU AS BRAINLIEST IF YOU KNOW THE ANSWER PLS GIVE ME A STEP BY STEP EXPLANATION!!
Answer:
a. (0,-5)
Step-by-step explanation:
X+3y=2 and y=2x+3
Please explain using substitution method.
- X + 3Y = 2 (*)
⇔X = 2 - 3Y (1)
- Y = 2X + 3 (2)
(1),(2)⇒ Y = 2(2 - 3Y) +3
⇔ Y = 4 - 6Y + 3
⇔ Y = 1 (**)
(*),(**)⇒ X + 3×1 =2
⇔ X = -1
please help me
I need help
Enter the repeating digit:
[tex] \frac{2 }{3} = 0. \frac{?}{?} [/tex]
Answer:0.6666...
Step-by-step explanation:
Dividing
Help me plz it’s due today
Answer:
10x²−9x
Step-by-step explanation:
10x²−10x−6+x+6
=10x²−10x−6+x+6
Combine Like Terms:
=10x²−10x−6+x+6
=(10x²)+(−10x+x)+(−6+6)
=10x²−9x
I hope this answer helps you out! Brainliest would be appreciated :)Answer:
10x^2=9x
Step-by-step explanation:
Add them together into one equation
10x^2 - 10x - 6 + x + 6
Now add like terms. The -6 and 6 cancel eachother out since they equal 0
10x^2 - 10x +x
You should get 10x^2 - 9x
Na função y = x² - 2x +1, temos que a = 1, b = -2 e c = 1, calcule as coordenadas do vértice da parábola
Answer:
(1, 0)
Step-by-step explanation:
x = -b / 2a
x = 2 / 2(1)
x = 2 / 2
x = 1
y = x^2 - 2x + 1
y = (1)^2 - 2(1) + 1
y = 1 - 2 + 1
y = -1 + 1
y = 0
vértice: (1, 0)
Help me quick i need helppp
[tex]\\ \sf\longmapsto (m-8)+(m-8)+(m-8)+(m-8)+(m-8)+(m-8)=12[/tex]
[tex]\\ \sf\longmapsto 6(m-8)=12[/tex]
[tex]\\ \sf\longmapsto 6m-48=12[/tex]
[tex]\\ \sf\longmapsto 6m=12+48[/tex]
[tex]\\ \sf\longmapsto 6m=60[/tex]
[tex]\\ \sf\longmapsto m=\dfrac{60}{6}[/tex]
[tex]\\ \sf\longmapsto m=10[/tex]
Answer:
M=14
Step-by-step explanation:
First make an equation - m÷6 =8Then shift 6 to 8 - m=6×8Answer - m=14what percentage of 225 is 11.25?
If x = 3 and y = 5 then which of the following expression has the value ( -8)
당신에게 도움이됩니다
[tex]( - 3) - 5 \\ = ( - 8)[/tex]
Will Mark Brainlest Help Please ,,,,
find the value of x and y
Step-by-step explanation:
(-1,0),m=2
(1-7),m=12
m=-4,(-1,-4)
Help me please I need this
Answer:
2 times
Step-by-step explanation:
3/4 × 2 = 6/4, simplified down is 3/2
Answer: the answer is a
PLEASE HEL URGENT 25 POINTS!!!
Write 0.0000012 in scientific notation
Answer:
0.0000012 = 1.2 x 10⁶ (that is the scientific notation)
Step-by-step explanation:
The decimal moves 6 places to the right
The 6 then becomes the exponent in a* 10^b
And (a) must be a 10 > number > 1
b = number of places the decimal moves
Answer:
1.2 * 10 ^6
Step-by-step explanation:
0.0000012
Move the decimal 6 places to the right
The 6 becomes the exponent in
a* 10^b a must be a number 1 or greater but less than 10
b is the the number of places the decimal moves (+ to the right, - to the left)
000001.2
Then the number becomes 1.2 * 10 ^6
The expression 2r^2+18x +40 has a greatest common factor of 2.
Once the GCF is factored out, what are the two binomial factors
left that complete the equation.
what are the 2 missing binomial factors?
2(x^2+9x+20)
2(x^2+5x+4x+20)
2{x(x+5)+4(x+5)}
2(x+5)(x+4)
The U.S. Mint produces quarters that weigh about 5.67 grams each. After the
quarters are produced, a machine weighs them. If the quarter weighs 0.02 gram more
or less than the desired weight, the quarter is rejected. Write and solve an equation to
find the heaviest and lightest quarters the machine will approve.
[tex]\to \bold{|x-5.67|=0.02}\\\\[/tex]
heaviest[tex]\bold{=5.69\ g\\\\}[/tex]
lightest[tex]\bold{=5.65\ g\\\\}[/tex]
Evaluating each expression:
[tex]\to \bold{q = -8}\\\\ \to \bold{r = -6}\\\\ \to \bold{t=3}[/tex]
Learn more:
brainly.com/question/20845315
Let's make some smores! Chocolate bars come in packs of 8 and graham crackers come in packs of 12. What is the smallest number of chocolate bars and graham crackers we would need to buy so we don't have any left over?
Answer:
3 chocolate bars and 2 graham crackers
Step-by-step explanation:
8 times 3 equals 24
12 times 2 equals 24